Sociodemographic and Clinical Factors Affecting Treatment Adherence in Adults with Attention Deficit and Hyperactivity Disorder - Erkan, Arzu; KILIÇ, ÖZGE; KILIÇ, ÖZGE; Semerci, Bengi (My University, 2022)
Background: This study aims to explore sociodemographic and clinical factors affecting medication adherence in adults with attention deficit and hyperactivity disorder and elicit dysfunctional domains and comorbidities with a focus on gender differences.